Sociocultural factors and social presence in an online learning environment - Pramela Krish,; Marlyna Maros,; Siti Hamin Stapa, (Penerbit UKM, 2012)
In a computer supported learning environment both in the synchronous and asynchronous mode, interaction is a prerequisite to facilitate learning. Hence to facilitate effective interaction, a good working team of learners and instructors is important. For this to happen, social presence is necessary to create sound social interaction for instructional effectiveness. Social presence is the ability of the instructors and learners to project their physical and emotional presence (Mardziah H. Abdullah (2004). However, the level of social presence in a virtual learning environment depends on the students’ and instructors’ sociocultural background. The sociocultural theory in language learning itself emphasizes the roles of interpersonal interaction rather than intrapersonal interaction.This article discusses some findings of a study on a computer supported collaborative learning environment. It shows how distance learners at an institution of higher learning in Malaysia responded to a questionnaire on the issues of social presence. The postings in the learner management system (LMS) and data from focus-group interviews were also analysed and discussed. The findings share some positive responses towards social presence in a virtual learning environment and calls for a more in-depth inquiry that will contribute to the literature on online collaborative learning in the Malaysian context.